6th International Maar Conference Abstracts - Liu, Jiaqi (IntechOpen, 2016)
This Book of Abstracts covers the abstracts presented at the 6th International Maar Conference (6IMC) in Changchun (China). The 6IMC conference sessions are focused on Maar and Environment Change, covering a wide spectrum of topics including: characteristics, mechanism, modeling and geological background of Monogenetic volcanic activities; volcanic evolution and spatial distribution regulation, resources, disaster, detecting, monitoring and societal responses of volcanic activity.